YEASTS: DIVERSITY IN KEFIR, PROBIOTIC POTENTIAL AND POSSIBLE USE IN ICE CREAM. - Cassanego, Daniela Buzatti (2015)
Kefir is a product made by the symbiotic fermentation of different microrganisms, resulting in a product with microbiological characteristics, physicochemical and sensory unparalleled. Bacterias, mainly of the gene Lactobacillus, and the yeasts are the main microrganisms that give rise of this product. The genres Kluyveromyces and Saccharomyces are the largest representatives of the yeasts found at Kefir’s microbiot. In relation of the probiotic potential of the yeasts, the one sold in drug form by mouth, is the Saccharomyces boulardii, however, researches are showing that other genres, other species and new strains of yeasts also had promising probiotic potential, but the researches don’t tell the application of this new probiotic yeasts in food. The aim of this review involved the achievement of a bibliographic review about different species and strains of yeasts found at Kefir’s samples by differents authors at the global level. The probiotic potential of yeasts was also studied, as well as the capability of probiotic microrganisms being added to ice cream. With conclusion it can be said that countless strains of yeasts are present in the Kefir’s symbiotic complex and, some of this possibly submit probiotic potential, that could being incorporated into ice cream, once the food have wide consumer acceptance and don’t uses the fermentation process in it’s preparation.